Behaviour change techniques used in lifestyle interventions that aim to reduce cancer-related fatigue in cancer survivors: a systematic review - Judith de Vries-ten Have; Renate M. Winkels; Ellen Kampman; Laura H.H. Winkens (BMC, 2023)
Abstract Background Lifestyle interventions that target dietary and/or physical activity behaviours may impact cancer-related fatigue in cancer survivors. Changing lifestyle may be especially difficult for cancer survivors suffering from cancer-related fatigue. To increase effectiveness of lifestyle interventions, behaviour change techniques (BCTs) can be applied. The aim of this review is to systematically describe which BCTs are applied in lifestyle interventions targeting cancer-related fatigue among cancer survivors who finished primary treatment. Methods PubMed, Scopus, PsycINFO, Cochrane Library and Web of Science were searched to identify randomised controlled trials (RCTs) of dietary and/or physical activity interventions targeting cancer-related fatigue in cancer survivors. The BCT taxonomy was used to code the BCTs that were applied in those interventions. BCTs that were reported in at least 25% of effective interventions were indicated as 'promising BCT', but only retained this classification when these BCTs were present in less than 25% of ineffective interventions. Results Twenty-nine RCTs were identified, of which 17 were effective in reducing cancer-related fatigue. The most frequently applied BCTs were Goal setting (behaviour), Instruction on how to perform the behaviour, Demonstration of the behaviour, Behavioural practice/rehearsal, and Credible Source. The BCT 'Generalisation of the target behaviour' was identified as promising. These results should be interpreted with caution as only three studies screened their participants on level of cancer-related fatigue and most studies focused only on physical activity. Furthermore, many studies did not include a measure for actual behaviour change and had no follow-up period after the intervention ended. Conclusions There is a need for studies that screen their participants on level of cancer-related fatigue and a need for studies that focus more on dietary behaviours as a possible intervention to reduce fatigue. Also, studies should include follow-up timepoints after the interventions ends to examine long-term behaviour change. Future lifestyle interventions should describe interventions in detail to allow for easier coding of BCTs, and report on actual behaviour change following the intervention. Interventions may apply the BCT 'Generalisation of the target behaviour' to incorporate lifestyle behaviours in daily life. This may increase the chance that interventions will effectively reduce cancer-related fatigue.